Faktor-Faktor yang Mempengaruhi Permintaan Ikan Patin (Pangasius sp.) di Kota Palembang - Lia Perwita Sari; Yulia Puspita Sari (Seminar Nasional Lahan Suboptimal, 2018)
Sari et al, 2019. Factors Affecting the Demand of Patin Fish (Pangasius sp.) in Palembang City. pp. 306-312. The need for animal protein derived from fish species continues to increase in line with population growth, income level, education level and public awareness of the importance of nutritious food. Along with increasing levels of fish consumption in South Sumatra, demand for catfish continues to increase. The purpose of this study was to analyze the demand for Patin fish in Palembang City. The research method uses survey methods. The research location was determined purposively, namely in the City of Palembang, namely in the Alang-alang Lebar Market, KM 5 Market, Cinde Market, Kuto Market, Soak Bato Market, Jakabaring Market, Kertapati Market and Multi Wahana Satellite Market. The withdrawal of the research sample was carried out using the accidental sampling method. Retrieval of respondents through this method is consumers who are buying Patin fish found in traditional markets to ask their opinions about what is needed to smooth this research as many as 40 people. The results of the study stated that the demand for catfish simultaneously was influenced by the purchase price of consumers, household income, age, number of household members and level of education. Partially, only the variable number of household members has a significant effect on the demand for Patin fish.